"Help, I Have Too Much Stuff!": Extreme Possession Attachment and Professional Organizers. Issue 2 (29th October 2014) - ROSTER, CATHERINE A.
<x xml:space="preserve">Abstract</x> Compulsive hoarding is a serious problem for consumers, their families, and the communities in which they live. Consumers naturally form attachments to their possessions. However, at the extreme end of the attachment spectrum, these attachments can undermine a consumer's well‐being. This study describes attachment styles exhibited by consumers who sought help from trained professional organizers (POs) to help them achieve their de‐cluttering goals. Narrative case descriptions were compiled from 28 trained POs across the United States using an Internet survey with mostly open‐ended questions. Interpretive analysis demonstrates how POs craft strategies to help clients let go of meaningful goods by considering the client's unique attachment profile and the temporal relevance of possessions to self. This study illustrates how POs help consumers improve their well‐being by unraveling possession attachments that threaten consumers' quality of life.